Public Perception of the COVID-19 Vaccine: Literature Review - Desyana Indira Putri; Budiyono; Ayun Sriatmi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Community perceptions of COVID-19 vaccines are responses or acceptance based on the information obtained regarding beliefs about the halal status of vaccines, willingness to be vaccinated, and the capacity of healthcare workers providing the COVID-19 vaccine. This is due to numerous issues affecting information about the COVID-19 vaccine. These facts have encouraged the government to enhance the COVID-19 vaccination program within the community. Objective: This study aims to explore and analyze the public perception of the COVID-19 vaccine. It seeks to identify key factors influencing attitudes towards the vaccine, including trust in health authorities, misinformation, demographic variables, and socio-political influences. The objective is to provide a comprehensive understanding of the drivers of vaccine acceptance and hesitancy to inform public health interventions. Method: This writing uses a literature review method. It involves searching for and filtering articles that meet predetermined criteria through inclusion criteria. In this writing, scientific articles were found using Google Scholar with search keywords "community perceptions," "knowledge," and "COVID-19 vaccine." Result: The study revealed a complex landscape of public perception regarding the COVID-19 vaccine. Trust in health authorities and exposure to misinformation emerged as significant factors impacting perceptions. There is a relationship between knowledge and community behavior, education level and vaccination history with knowledge, religion with community attitudes, and COVID-19 vaccination history. Conclusion: Knowledge influences community perceptions of the COVID-19 vaccine. Therefore, it is necessary to provide comprehensive and equitable information to all communities about the usefulness, safety of the COVID-19 vaccine, and all updated information regarding the COVID-19 vaccine.